Meta‐analysis evaluating resting laryngeal endoscopy as a diagnostic tool for recurrent laryngeal neuropathy in the equine athlete. (6th August 2018) - Elliott, S.; Cheetham, J.
Summary: Background: Resting endoscopy has commonly been used as a method to predict laryngeal function at exercise. Objectives: To perform a meta‐analysis to determine the sensitivity and specificity of resting laryngeal endoscopy to predict clinical recurrent laryngeal neuropathy at exercise. Study design: Meta‐analysis. Methods: Manuscripts were included if data were available for both resting and exercising airway function on all or a subset of horses. Normal resting endoscopy was defined as laryngeal grades 1 or 2 on a 4‐/7‐point scale or 1, 2 or 3 on a 5‐point scale and normal dynamic endoscopy as a dynamic laryngeal grade A. Results: Twelve studies including 1827 horses were evaluated. A small proportion of horses with grade 1 or grade 2 laryngeal function at rest, 3.5 and 11.9%, respectively, were identified as having abnormal laryngeal function at exercise. Within the horses with grade 3 laryngeal function at rest, 16% were classified as grade A, 26.4% as grade B and 57.6% as grade C at exercise. Worsening subgrades within resting grade 3 demonstrated an increasing proportion of complete or partial paralysis at exercise. The sensitivity and specificity of resting endoscopy was 74.4 and 95.1%, respectively, and the positive and negative predictive values were 85.6 and 90.5% respectively. Main limitations: Use of two separate grading systems for evaluating resting laryngeal function. Other forms of dynamic airway collapse were not evaluated. Conclusions: Resting endoscopy is sensitive and highly specific for predicting laryngeal function at exercise. Dynamic endoscopy is important to assess multiple causes of airway collapse.